Economic and technical aspects of smallholder milk production in Northern Tanzania. - Zalla, T.M. (Michigan State University, 1982)
This study provides data on smallholder milk production on mount Kilimanjaro. It analyzes alternative smallholder milk production systems in current use there and outlines a strategy for expanding smallholder milk production on the mountain. Data for the study were gathered in 1973 from a single visit farm management survey of over 680 randomly selected households in the coffee-banana zone of Mount Kilimanjaro. These are discussed and analyzed in the context of post-Hicksian neo-classical economic theory as well as the political and social context of Tanzania.Technical data are supplemented with information on production traits and management practices for cattle available from elsewhere in Africa. The study estimates that zebu cattle and grade cattle each accounted for about one-half of cattle milk production on the mountain in 1973 even though only 12 percent of all cattle were grade dairy animals. Lactation milk production averages around 380 liters for zebu cattle and 1,470 liters for grade cattle, net of milk suckled by calves. Reducing calf mortality and the calving interval by making veterinary and breeding services more easily available to farmers appear to be the only two factors that are likely to lead to substantial increases in milk production by zebu cows. For grade cows the marginal value product of resources invested in providing water, salt, grain products and forage are all considerably in .excess of their marginal factor cost and the potential for increasing milk production quite significant. Overall, variables over which a well-organized extension service can have some influence explain about 70 percent of the variation in milk production for grade cows. The economic analysis of returns to alternative milk production systems shows that upgrading zebu cattle yields returns to resources that are considerably above their opportunity cost and not far below the returns available from a pure grade dairy enterprise that requires much more sophisticated management and over twice the capital investment. The major constraint on expansion of upgraded and grade cattle milk production is a dearth of good quality grade bulls and poorly functioning extension and artificial insemination programs. Forage supplies are also a problem. Improvement of extension and veterinary services and research into forage crops that can be integrated into existing farming systems merit immediate attention.